Pengaruh Sosialisasi Badan Amil Zakat Nasional terhadap Minat Muzaki Membayar Zakat - Delvi Hamsiska Putri; Iwan Siswanto; Seri Yanti Siagian (AL-Muqayyad, 2021)
This study aimed to determine whether the socialization of BAZNAS affects the interest of Muzaki in distributing zakat through the National Amil Zakat Agency of Indragiri Hilir Regency. This research was quantitative. The data were analyzed using a simple linear regression method with the help of the Statistical Product and Service Solutions (SPSS) 23. The results of the data analysis showed the tcount was 20.985 so that, ttable 1.651 < tcount 20.985 with a significance of 0.000 under 0.05. Thus, it concluded that the socialization of BAZNAS on the interest of Muzaki in paying zakat through the National Amil Zakat Agency in Tembilahan City has a significant influence.